Історія інтродукції видів роду Sambucus L. в Україні - Kolisnyk, L.N.; Klymenko, S.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
On the basis of literature data the history of introduction of species of Sambucus L. in Ukraine is presented. Data about the structure of Sambucus species collections in botanical gardens of Ukraine are cited.